Some bacteriological properties of the rhizosphere of pineapple cultivated in suoihai farm, Ba Vi district, Ha Tay province - Anh, Nguyen Minh; Ha, Pham Thanh; Quynh Mai, Nguyen Thi; Dung, Nguyen Ngoc (Academia Journal of Biology, 2014)
The densities of total carbohydrate heterotrophic, fluorescent pseudomonad, bacilli, microaerobic, aerobic nitrogen-fixing and phosphate dissolving bacteria in the rootfree soils and in roots of pineapples cultivated in the Suoihai farm at different stages were studied. In general, the density of the investigated bacteria groups in soils as well as in roots was not high, from some to hundreds million cells per gram of wet sample. The obtained dates showed that the pineapple roots did not appear to be an attractive medium for the occurence of bacteria.